Analysis of the Intensity of Playing Online Games Among Probolinggo City Student - Robbiah Ratna Swari Hibbatullah; Naura Afkarina; Iswandi Iswandi (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2025)
This study aims to examine the intensity of online game playing among students in Probolinggo City. The research employed a descriptive quantitative design, with data analyzed using category-based assessment techniques. The findings indicate that the intensity of playing online games among students obtained an average score of 2.7, which falls into the moderate category. Furthermore, when viewed from aspects of motivation, influence, and the impacts of online game playing, the overall average score also reached 2.7, indicating a moderate level. These results suggest that students in Probolinggo City generally engage in online gaming at a moderate intensity. Based on these findings, it is recommended that schools, families, and the wider community pay closer attention to students’ online gaming habits in order to manage playing time effectively and minimize potential negative effects associated with excessive online game use.